The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations FOREWORD CLEARLY, since you are reading this book, you are either a tenant or intending to be one. As a tenant, you will be living on the property of another person ... it is his house, but YOUR HOME. There is a difference here and a big one, for you can have a house without having a home. A home is what you make it. It should be a place of leisure and comfort. It should compel husband, wife and children to like it, to wish to be in it. It should be a place which trains children to the proper use of comfort and leisure, proper consideration for others, and the proper way of life and living. FIRST EDITION 1937 177/5/8/2